Analisis Campur Kode dan Alih Kode Dalam Program Game Show TWK Season 2 Pada Akun Youtube Narasi - Charlina, Charlina; Nabila, Nabila; Oktanur, Ory Dwi; Sari, Tiara Yuyun; Zaini, Nadia (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2022)
This study is motivated by a code-mixing and code-switching phenomenon in Indonesian society's communication as bilinguals and multilingual. In Indonesian society, the phenomenon of code-mixing and code-switching also occurs on social media platforms, one of which is YouTube. This study analyzes forms of code-mixing and code-switching in Narasi YouTube videos. This research aims to describe (1) the forms of code-mixing and code-switching and (2) factors that cause code-mixing and code-switching in the TWK season 2 video program on Narasi YouTube. This is a qualitative study that identifies the data using descriptive methods. Data collection techniques included observation, listening, and note-taking. The results of this study reveal that there is external code-mixing and switching, as well as internal and external code-switching. In the videos of the TWK season 2 episodes 1–14 on Narasi YouTube, code-mixing is more dominant than code-switching. Factors that affect code-switching and code-mixing to evoke a sense of humor, identification indicators, speaker factors, situations, and topic changes.